PERANAN PENYULUH PERTANIAN LAPANG (PPL) DALAM ADOPSI PENGELOLAAN TANAMAN TERPADU (PTT) USAHATANI PADI SAWAH DI KECAMATAN SEPUTIH RAMAN - Rendi Henda Ramadhan; Begem Viantimala; Serly Silviyanti (Lampung University, 2019)
This study aims to determine the level of role of agricultural extension workers on adopting integrated crop management, determine the level of adoption of integrated crop management of paddy rice in increasing productivity, analyze the relationship between the role of agricultural extension workers and adoption of integrated crop management, and analyze the relationship between adoption of integrated crop management and the productivity of lowland rice. Determination of sampling conducted by proporsional random sampling and obtained 99 people divided into eight agricultural extension work areas. The research data is analyzed by descriptive and inferential statistics of Rank Spearman correlation test. The results of the study showed that the role of field agricultural extension workers in the management of integrated crops of paddy fields was in the medium classification; these roles included activities in education, dissemination, facilitation, consultation, supervision, monitoring, and evaluation. Adoption of integrated plant management based on the use of quality seeds and planting systems, irrigation, fertilization, control of plant pests, handling of harvests to post-harvest were in the medium classification. The role of field agricultural extension workers was significantly correlated with the adoption of integrated crop management, while adoption of integrated crop management was related to the productivity of lowland rice.Key words : adoption, agricultural extension workers, integrated crop management, paddy, roles